Estancia hospitalaria prolongada asociada a mortalidad en Hospital Regional Docente de Trujillo, 2014 - Herrera-Viloche y Colls., Marie (2018)
Prolonged hospital stay, considered one that exceeds 13 days, generates additional costs to the hospital, poor access to inpatient services for new patients and risk of acquiring nosocomial infections, as well as social and family crisis. This study aims to determine the specialties and age groups associated with prolonged stay of Regional Hospital of Trujillo in 2014. 11866 hospitalizations were recorded, and of these 1193 had prolonged hospital stay, of which 56.58% were male and 43.42 % female. The departments of medicine and surgery with 45.1% and 31.3% and the extreme age group over 61 and under 20 with 29.76% and 27.75% were those with longer hospital stay. Patients with prolonged hospital stay and mortality, gives an odds ratio of 3.276, with IC 2615-4104, with p = 0.0000.